Fun and games - Finnish children's ideas for the use of digital media in preschool - Pekka Mertala (Universitetsforlaget, 2016)
This study has used drawings from and interviews with 5-6 year-old Finnish children (N=103) to explore their ideas for the use of digital media in preschool. The main findings, based on data driven analysis, were the following: Playing commercial digital games was the most popular activity followed by media production, mainly photographing. Computers, tablets and cameras were the most popular devices. Digital media was understood to be more about leisure than learning. Pedagogical implementations are discussed. Keywords: Digital media, preschool, early childhood education, digital games